An essential guide to aging well : older, wiser - Bethell, Katharine (New York : Routledge, 2020)
"This book is a refreshingly honest self-help guide to aging well. It encourages readers to dispel gloom or overcome denial around the subject of aging and offers advice in a realistic, non-prescriptive format. Written in a conversational style, An Essential Guide to Aging Well motivates its readers to be curious about this time of life, and to design the best possible version of it for themselves"--
OCLC-licensed vendor bibliographic record.
Keywords: Aging -- Social aspects; Aging -- Psychological aspects; Quality of life; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Developmental / Adulthood & Aging